Adherence to Coronavirus Disease 2019 Preventive Measures in a Representative Sample of the Population of the Canton of Vaud, Switzerland - Audrey Butty; Nolwenn Bühler; Nolwenn Bühler; Jérôme Pasquier; Julien Dupraz; Vincent Faivre; Sandrine Estoppey; Cloé Rawlinson; Semira Gonseth Nusslé; Murielle Bochud; Valérie D'Acremont; Valérie D'Acremont (Frontiers Media S.A., 2022)
Objectives: We quantified adherence to COVID-19 preventive measures and explored associated factors, after the first and during the second Swiss epidemic waves.Methods: With an observational cohort study in a representative sample of individuals aged 15 years and more, we analysed the association between self-reported adherence to COVID-19 preventive measures (respect of simple hygiene rules; respect of social distancing rules; wearing a mask) and socio-demographic factors, the existence of a chronic disease, and the existence of a previous confirmed COVID-19 episode.Results: Highest adherence was to simple hygiene rules, followed by social distancing rules and mask wearing, with a slight decrease for simple hygiene rules and a strong increase for mask wearing between visits. Men were significantly less likely to respect simple hygiene rules and wear a mask in public. Participants aged 65 years and more (versus 25-64 years) and those with at least one chronic disease (versus none) were two times more likely to respect social distancing rules and wear a mask.Conclusion: Adherence to social distancing rules and mask wearing was rather poor, especially compared to other countries.